2022
DOI: 10.3389/fpsyg.2022.809629
|View full text |Cite
|
Sign up to set email alerts
|

Water and Meadow Views Both Afford Perceived but Not Performance-Based Attention Restoration: Results From Two Experimental Studies

Abstract: Attention Restoration Theory proposes that exposure to natural environments helps to restore attention. For sustained attention—the ongoing application of focus to a task, the effect appears to be modest, and the underlying mechanisms of attention restoration remain unclear. Exposure to nature may improve attention performance through many means: modulation of alertness and one’s connection to nature were investigated here, in two separate studies. In both studies, participants performed the Sustained Attentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
2
4
0
Order By: Relevance
“…The null effect found in the current study is consistent with existing studies that have failed to replicate the effect of viewing virtual natural environments on cognitive functions (Cassarino, Tuohy, & Setti, 2019; Emfield & Neider, 2014; K. A. Johnson et al, 2022; Kuziek, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The null effect found in the current study is consistent with existing studies that have failed to replicate the effect of viewing virtual natural environments on cognitive functions (Cassarino, Tuohy, & Setti, 2019; Emfield & Neider, 2014; K. A. Johnson et al, 2022; Kuziek, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…In summary, the present study showed that viewing videos with natural scenery do not have any effect on working memory capacity in a high-powered pre-registered within-subject experimental study. Consistent with existing studies that failed to replicate the positive cognitive effect of viewing pictures of nature settings (e.g., Cassarino, Maisto, et al, 2019; K. A. Johnson et al, 2022; Neilson et al, 2021), the current study reaffirms this conclusion that virtual nature simulation does not reliably restore attentional resources.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The ‘miscellaneous’ category ( n = 23) includes various items that did not seem to fit into any of the other categories, but still examined mental health. This includes outcomes such as sleepiness, smoking behavior or emotional eating patterns [e.g., ( 106 , 118 , 119 )]. Some of these studies also used validated tools, such as the Karolinska sleepiness scale, which assesses sleepiness in regard to the psycho-physical state [e.g., ( 119 )].…”
Section: Resultsmentioning
confidence: 99%